Our class : trauma and transformation in an American prison - Hedges, Chris (Simon & Schuster, 2021)
"Chris Hedges's powerful memoir of his year of teaching inmates in a maximum-security New Jersey prison takes readers into the lives of men who were all but destined to become incarcerated because of their impoverished and dangerous childhoods and shows why criminal justice reform is so essential"--